The Influence of Leadership Style, Work Climate and Facilities and Infrastructure On Teacher Performance with Motivation Work as Variables Mediation at the Sub- district Public Elementary School Sirampog Brebes Regency - Laelatul Khoeriyah; Suwito Eko Pramono; Sugi (Educational Management, 2026)
This study aims to determine the role of work motivation in mediating the influence of leadership style, work climate, and infrastructure on the performance of public elementary school teachers in Sirampog Regency. This study was conducted using a quantitative method, and data collection was carried out using valid and reliable research instruments. The population in this study consisted of public elementary school teachers, with a sample selected using the Slovin formula. Data analysis was conducted using multiple linear regression, mediation testing with the Sobel test, and path analysis. The results of the study indicate that work motivation as a mediating variable is able to mediate the influence of leadership style and work climate on teacher performance, as evidenced by significant results and calculated Z values exceeding the critical Z value. On the other hand, work motivation does not have a positive and significant mediating effect on the relationship between infrastructure and teacher performance, as indicated by non-significant results and calculated Z values below the critical threshold. Overall, the findings show that improving work motivation, leadership style, and a supportive work climate has a significant influence on enhancing teacher performance.